Skimming and Scanning Techniques to Assist EFL Students in Understanding English Reading Texts - QISMULLAH YUSUF; YUNISRINA QISMULLAH YUSUF; BURHANSYAH YUSUF; ALFA NADYA (Universitas Jambi, Indonesia, 2017)
This research aimed to find out whether the skimming and scanning techniques (SST) can improve EFL students’ English reading comprehension in recount texts, especially on identifying the main ideas and detail information, in a senior high school in Meulaboh, Aceh, Indonesia. A number of 32 eleventh grade students participated in this study, and the one group pre-test and post-test design were used. Data collection was from a pre-test and a post-test. In analyzing the data, statistics was used. The results showed that the mean score of the pre-test was 45 and the post-test was 65, with 20 points of improvement. Furthermore, the result of t-test was 4.7, while the critical value of 0.05 significant level was 2.4, with the degree of freedom at 23. Since t-test>t-score, thus SST improved the students’ reading comprehension in this study. Nevertheless, the paper further discusses some setbacks while implementing SST in the classroom.